Empowering communities to manage natural resources: case studies from Southern Africa - Shackleton, S.; Campbell, Bruce M. (SADC Wildlife Sector-Natural Resources Management Programme and CSIR, 2000)
This report consists of a series of individual country papers prepared for a study on devolution, community empowerment and power relations in community-based natural resource management (CBNRM) in the SADC region. Case studies were undertaken during 1999 in eight southeastern/eastern African countries; Botswana, Lesotho, Malawi, Namibia, Zambia, Zimbabwe, South Africa (two separate studies) and Tanzania. These studies drew mainly on existing literature and the direct experiences of authors in CBNRM initiatives in their own countries. Each paper was structured under a common framework using standardised headings. Limited fieldwork was carried out in some countries. The study attempted to address the key questions. Are the approaches to CBNRM in the selected southern African countries truly community-based in that decision-making and regulation resides with local resource users or rights holders, and the benefits of resource management accrue back to the local community? If not, where does control lie, and what are the institutional arrangements and other factors which have contributed to this imbalance in power and blocked the achievement of devolution to a local level? What are the lessons learnt from the different case studies in terms of shifting the balance of power to ensure more equitable CBNRM? Within this context, each country paper investigated devolution and power relations’ issues within selected CBNRM case studies. The papers examined: the extent to which policy and legislation devolves significant control over decision-making and benefits flows directly to communities and community institutions; the relationships between the community institutions and external institutions such as local authority structures, NGOs, donor agencies and the private sector; the power and legitimacy of these different structures; and the relationships between different groups and individuals within the community and the conflict that has emerged over CBNRM issues.